Alley-cropping in West Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
The University of Hohenheim in West Germany has set up a regional research programme which will produce and improve agricultural production technologies targeted on small-scale farmers in West Africa. Work is now underway at various collaborating...